MODEL PEMBELAJARAN PROBLEM BEASIC LEARNING PADA MATA PELAJARAN QUR’AN HADIST DI MTsN 1 NAGAN RAYA - Ibnu Hajar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This research was conducted at MTsN 1 Nagan Raya for weeks with a quantitative method with analysis using a simple frequency distribution. Data collection techniques were taken by distributing questionnaires, interviews, observations, documentation and test instruments. The results showed that: first, the learning of fiqh at MTsN 1 Nagan Raya was going well because the teacher used various learning methods according to the teaching material and the evaluation of fiqh learning was carried out by giving assignments to students. Second, in applying the PBL learning model to fiqh subjects, the method used is to explain learning materials, group divisions, discuss, strengthen materials and conclude learning outcomes. Third, the PBL learning model has a very beneficial effect on students, namely making students more skilled, motivated, active and easy to understand the material. Fourth, the obstacles encountered during the learning process are diverse student abilities, lack of student focus in learning, limited learning time, students' physical conditions and classroom conditionsKeywords: Problem Based Learning, Qur’an Hadist, Learning.